Interporosity Flow Between Matrix and Fractures in Carbonates: A Study of its Impact on Oil Production; Arabian Journal for Science and Engineering; Vol. 49 - Martyushev D. A. Dmitry Aleksandrovich; Ponomareva I. N. Inna Nikolaevna; Davoodi Sh. Shadfar; Kadkhodaie A. Ali (2024, 2024)
Title screen